Ottoman/Turkish Visions of the Nation, 1860–1950 - Gürpınar, Doğan; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Seeing the critical phase in the construction of a Turkish historical imagination between 1860 to 1950 disregarding the political disruptions, this book demonstrates how history and historical imagery had been instrumental in the nation-building process.
Keywords: History, Modern; Imperialism; Social history; Europe-History.; Civilization-History.; Modern History; Imperialism and Colonialism; Social History; European History; Cultural History